1997
DOI: 10.1183/09031936.97.10061345
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of the amount of salbutamol available for inhalation from different formulations used with different spacer devices

Abstract: The hydrofluoroalkane formulation delivers more salbutamol than the conventional formulation when used either with the Aerochamber® or Nebuhaler® spacer. This may be because less drug is deposited in the spacer from the hydrofluoroalkane formulation, which is emitted from the metered-dose inhaler at a slower speed and occupies a smaller volume than the conventional formulation. The observed difference in drug delivery may be important for patients changing formulations, and in severe asthma, where high doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 13 publications
3
31
0
1
Order By: Relevance
“…We washed the spacer devices with lukewarm water and allowed them to dry at room air. Clark (20) demonstrated that washing a plastic spacer device (Volumatic, GlaxoSmithKline) in water was as effective as an antistatic paint in reducing the effects of static charge on salbutamol delivery, but other authors (8,(17)(18)(19) have shown that washing in water alone had a variable and unpredictable effect on spacer electrostatic charge. That in vivo effects of static charge may not support the in vitro results has been further demonstrated in a recent crossover study in 90 young children with asthma (21).…”
Section: Discussionmentioning
confidence: 99%
“…We washed the spacer devices with lukewarm water and allowed them to dry at room air. Clark (20) demonstrated that washing a plastic spacer device (Volumatic, GlaxoSmithKline) in water was as effective as an antistatic paint in reducing the effects of static charge on salbutamol delivery, but other authors (8,(17)(18)(19) have shown that washing in water alone had a variable and unpredictable effect on spacer electrostatic charge. That in vivo effects of static charge may not support the in vitro results has been further demonstrated in a recent crossover study in 90 young children with asthma (21).…”
Section: Discussionmentioning
confidence: 99%
“…Os inaladores dosimetrados podem ser utilizados eficientemente em todas as idades, durante a respiração normal, desde que acoplados a um espaçador [5][6][7] , e permitem ministração rápida da medicação, sendo assim melhor tolerados por crianças pequenas; além disso, em torno de 20% das partículas geradas atingem as vias aéreas inferiores 5,[8][9][10][11][12] , com padrão de deposição mais previsível e menos variável que os nebulizadores. Apesar dessas vantagens, os inaladores dosimetrados com espaçadores ainda não substituíram os nebulizadores na maioria dos serviços de emergência e hospitais pediátricos.…”
Section: Introductionunclassified
“…[11][12][13] In addition, selection of spacer design may also be unimportant for drug delivery to the periphery of the lung. 8,14 Dubus et al showed salbutamol (albuterol) responses were not significantly different between spacer devices when an HFA134a formulation was used. 11 It has also been shown that use of a spacer with or without an HFA formulation did not change the plasma profiles of beclomethasone dipropionate.…”
Section: Introductionmentioning
confidence: 99%
“…8 Similarly, a study comparing a HFA134a formulation in either the Aerochamber or the Nebuhaler spacer devices showed FPDs were equivalent with either design. 14 In addition, it has recently been reported that solution pMDIs containing HFA134a have multimodal particle size distributions. 15 Two dominating particle size modes were located at around 1 µm and 10 µm or above.…”
Section: Introductionmentioning
confidence: 99%